2021
DOI: 10.3390/ijms22189719
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of LncRNA in Bovine Mammary Epithelial Cell Injuries Induced by Escherichia Coli and Staphylococcus Aureus

Abstract: Escherichia coli and Staphylococcus aureus are two common pathogenic microorganisms that cause mastitis in dairy cows. They can cause clinical mastitis and subclinical mastitis. In recent studies, lncRNAs have been found to play an important role in the immune responses triggered by microbial inducers. However, the actions of lncRNAs in bovine mastitis remain unclear. The purpose of this study was to investigate the effects of bovine mammary epithelial cell injuries induced by treatment with E. coli and S. aur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…In this study, the expression profiles of mRNAs and lncRNAs from healthy cows and subclinical mastitis cows were characterized, and the functions of 287 DEGs, 70 DELs, and 1,621 DAS genes were annotated, obtaining a number of significantly enriched pathways. Notably, the NOD-like receptor signaling pathway, cytokine-cell receptor interaction, Toll-like receptor signaling pathway, and S. aureus infection pathway were also significantly enriched in the available studies of bovine mammary epithelial (BME) cells ( Wang et al, 2016 ; Wang et al, 2020a ; Lin et al, 2021 ), suggesting that these pathways play important regulatory roles in the pathogenesis of mastitis in blood and breast tissue. Subsequently, based on target gene prediction and QTL database annotation, the results showed that the lncRNAs MSTRG25101.2, MSTRG.56327 0.1, and MSTRG.18968.1, which are adjacent to the SCS QTL and SCC QTL, regulate the expression levels of genes NOD2 , CXCL8 , OAS2, and TLR4 , which are involved in the NOD-like receptor signaling pathway, Cytokine-cytokine receptor interaction, and Toll-like receptor signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the expression profiles of mRNAs and lncRNAs from healthy cows and subclinical mastitis cows were characterized, and the functions of 287 DEGs, 70 DELs, and 1,621 DAS genes were annotated, obtaining a number of significantly enriched pathways. Notably, the NOD-like receptor signaling pathway, cytokine-cell receptor interaction, Toll-like receptor signaling pathway, and S. aureus infection pathway were also significantly enriched in the available studies of bovine mammary epithelial (BME) cells ( Wang et al, 2016 ; Wang et al, 2020a ; Lin et al, 2021 ), suggesting that these pathways play important regulatory roles in the pathogenesis of mastitis in blood and breast tissue. Subsequently, based on target gene prediction and QTL database annotation, the results showed that the lncRNAs MSTRG25101.2, MSTRG.56327 0.1, and MSTRG.18968.1, which are adjacent to the SCS QTL and SCC QTL, regulate the expression levels of genes NOD2 , CXCL8 , OAS2, and TLR4 , which are involved in the NOD-like receptor signaling pathway, Cytokine-cytokine receptor interaction, and Toll-like receptor signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This response occurs through an inflammatory-related pathway ( 10 13 ). Some studies have confirmed the immune response of mastitis in S. aureus and E. coli infection ( 14 18 ). However, the regulatory function of noncoding RNA and epigenetic modification is ignored.…”
Section: Introductionmentioning
confidence: 87%
“…LncRNAs regulate inflammatory factor expression and inflammatory signaling pathways by interacting with specific miRNAs, mRNAs, and proteins at the transcriptional and post-transcriptional levels, ultimately alleviating inflammatory damage. At present, some progress has been made regarding research on lncRNAs in the diagnosis and treatment of inflammatory diseases such as acute kidney injury (AKI) [ 64 ], liver inflammation [ 65 ], ALI [ 66 ], OA [ 67 ], mastitis [ 68 ], and neuroinflammation [ 69 ] ( Table 2 ). This section primarily focuses on the roles of lncRNAs in inflammatory diseases, to provide some reference for further research on lncRNAs in inflammatory diseases.…”
Section: Role Of Lncrnas In Inflammatory Diseasesmentioning
confidence: 99%